Effects of Short and Prolonged Mild Intracellular Nitric Oxide Manipulations on Various Aspects of Insulin Secretion in INS-1E β-Cells - Natali, A.; Santini, E.; Delbarba, A.; Baldi, S.; Venturi, E.; Tulipani, A.; Nisoli, E.; Ferrannini, E. (Experimental and Clinical Endocrinology & Diabetes, 2012)
We aimed at evaluating the impact of short and prolonged mild manipulations of intracellular nitric oxide (NO) bioavailability on the main features of insulin secretion and whether NO promotes mitochondrial biogenesis in isolated β-cells.INS-1E β-cells were exposed to either the intracellular NO donor, hydroxylamine (HA), or the NO synthase inhibitor, L-nitro-arginine-methyl-ester (l-NAME), at concentrations lower than 2.0 mM. Glucose and arginine-induced insulin secretion (GIIS and AIIS) were measured after short (1 h) or prolonged (48 h) exposure to l-NAME 1.0 and 2.0 mM or HA 0.4 and 0.8 mM, lower concentrations were also evaluated for the 1 h effects. Basal insulin secretion (BIS), with either HA or l-NAME added to culture media, and peroxisome proliferators-activated receptor γ coactivator 1α (PGC-1α), nuclear respiratory factor-1 (NRF-1), and mitochondrial DNA transcription factor-A (Tfam) gene expression during chronic HA supplementation were also measured.Neither l-NAME nor HA affected insulin release at glucose 3.3 mM or in cell culture (BIS). Both short and prolonged cell exposure to l-NAME potentiated GIIS though with a flat dose-response curve while HA inhibited GIIS only at the highest concentration. AIIS was prevented by short exposure to l-NAME and potentiated by HA, while it did not respond to prolonged incubations. Prolonged cell exposure to HA had no effect on PGC-1α, NRF-1 or Tfam gene expression.In INS1E cells an intact NO synthesis is necessary to limit insulin release in response to acute glucose gradients and to fully respond to arginine while intracellular NO enrichment above the physiologic levels further inhibits GIIS and potentiate AIIS only when excessive. Prolonged NO manipulations do not affect AIIS, BIS or mitochondrial biogenesis.
Keywords: nitric oxide; insulin secretion; mitochondrial biogenesis